Pengaruh Budaya pada Penamaan Semantis Alat Musik Tradisional Tasikmalaya - Moh. Hafidz Assidiq Syam; Muhammad Aghniya Tasaq; Jessica Nabila; Aveny Septi Astriani (Departement of Mathematics Education, 2024)
This research aims to study more deeply how culture can influence the semantic naming of objects, in this case Karinding, Lodong Gejlig, and Tarawangsa. The method used in this research is descriptive qualitative. The data collection technique used is the document study technique. The data in this research are three traditional Tasikmalaya musical instruments, namely Karinding, Lodong Gejlig, and Tawarangsa. This research concludes that each object has various names depending on the culture or region where the object was created. Naming in all three includes imitation of sounds, mention of distinctive characteristics, mention of parts, materials, shortening, and new naming (Arbitrary). Not only that, the semantic naming that occurs in these three also cannot be separated from the role of culture and society where the musical instruments were created.